Increased platelet reactivity in dyslipidemic patients with coronary artery disease on dual anti-platelet therapy - Bernhard Jäger (Termedia Publishing House, 2018)
Introduction The optimal duration of dual anti-platelet therapy (DAPT) following percutaneous coronary intervention (PCI) is still a matter of debate. Biomarkers may help to identify patients who will benefit from extended DAPT. The aim of the study was to test the interaction between lipid parameters and platelet function in patients with coronary artery disease (CAD) on DAPT.